2018
DOI: 10.1515/iss-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and reconstructive surgery efforts in severe hand injuries

Abstract: Introduction:Severe hand trauma, leading to extensive skeletal and tissue defects, requires plastic surgical reconstruction of the highest level aiming at maximizing function and aesthetics. The intention of this study was to investigate clinical parameters and resource consumption connected with severe hand injuries, with specific emphasis on a follow-up evaluation of quality of life after the reconstruction process.Materials and methods:In this retrospective study, we evaluated patients with severe hand inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Clear perfusion damage of the tissue and lack of possible revascularization are hard criteria for amputation of the affected tissue. However, for areas that have suffered massive damage but are eligible for preservation, it is difficult to decide whether early amputation and bionic prosthetic care will benefit with shorter inpatient stay, interval for outpatient follow-up, and time to reintegration in professional life [15]. In addition to post-traumatic stress disorder associated with acute hand trauma, the need for repetitive corrective interventions also causes other psychological disorders such as anxiety, depression, and social isolation caused by disfigurement and pain [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear perfusion damage of the tissue and lack of possible revascularization are hard criteria for amputation of the affected tissue. However, for areas that have suffered massive damage but are eligible for preservation, it is difficult to decide whether early amputation and bionic prosthetic care will benefit with shorter inpatient stay, interval for outpatient follow-up, and time to reintegration in professional life [15]. In addition to post-traumatic stress disorder associated with acute hand trauma, the need for repetitive corrective interventions also causes other psychological disorders such as anxiety, depression, and social isolation caused by disfigurement and pain [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interpersonal perceptions of patients with bionic technologies can vary based on the technology [14]. Although the aim of reconstructive surgery is to restore esthetic and function by reconstructing anatomical structures, the reconstructive process is long and elaborate and may not result in the desired functionality and appearance [15].…”
Section: Introductionmentioning
confidence: 99%
“…The overall outcome in which all five parameters were achieved was 87.5 % with the main aim being resumption of daily activities in a shorter time and with minimal short term and long term complications. [13][14][15] These local flaps were able to achieve adequate wound coverage in almost 97% of defects making them a very reliable coverage option. Jiao et al in their article of clinical experience of multiple flaps for the reconstruction of dorsal digital defects achieved adequate coverage with minimal complications.…”
Section: Discussionmentioning
confidence: 99%
“…4 Prolonged recovery in hand injuries can reduce the health related quality of life (HRQoL) in patients. 5,6 They can have significant impact on the rehabilitation and well-being of the patient in the long term. 7,8 Patients with other associated injuries, low socioeconomic class, female gender and people with suboptimal outcomes report a decrease in the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Patients with other associated injuries, low socioeconomic class, female gender and people with suboptimal outcomes report a decrease in the quality of life. 5,9 Recent studies have shown that there is a decrease in the number of surgeons who would respond to the emergency department calls related to hand Reconstructive options given for each defect.…”
Section: Introductionmentioning
confidence: 99%